2003
DOI: 10.1021/nl034620k
|View full text |Cite
|
Sign up to set email alerts
|

Highly Ordered Assemblies of Au Nanoparticles Organized on DNA

Abstract: We developed a simple method for highly ordered assemblies of gold nanoparticles (AuNPs) along DNA molecules on substrates, and achieved assemblies with well-aligned and long-range order by using well-stretched DNA templates. In addition, oxidized aniline-capped AuNPs (AN−AuNPs) prepared in this study were strongly attached to DNA. Two different assembly methods were carried out, and consequently continuous depositions and necklace-like depositions of AN−AuNPs along DNA molecules were achieved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
171
1
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
3
1

Relationship

4
6

Authors

Journals

citations
Cited by 246 publications
(177 citation statements)
references
References 27 publications
3
171
1
2
Order By: Relevance
“…[12][13][14][15] Selfassembly technology can be effectively used to assemble wellorganized one-to three-dimensional structures, and interparticle connections can be constructed at a controllable single-particle level. [16][17][18] Among inorganic materials, metal NPs are one of the most frequently studied materials for applications to various nanotechnology-oriented devices, 19,20 and their distinct shapes and combinations, such as nanobarcodes, nanorods, and nanowires, can contribute unique functions. 21,22 We have recently reported the electroconductivity of gold NP ͑AuNP͒ array films, which consisted of AuNPs and thiol molecules as the binder.…”
mentioning
confidence: 99%
“…[12][13][14][15] Selfassembly technology can be effectively used to assemble wellorganized one-to three-dimensional structures, and interparticle connections can be constructed at a controllable single-particle level. [16][17][18] Among inorganic materials, metal NPs are one of the most frequently studied materials for applications to various nanotechnology-oriented devices, 19,20 and their distinct shapes and combinations, such as nanobarcodes, nanorods, and nanowires, can contribute unique functions. 21,22 We have recently reported the electroconductivity of gold NP ͑AuNP͒ array films, which consisted of AuNPs and thiol molecules as the binder.…”
mentioning
confidence: 99%
“…[40][41][42][43] The self-assembly technology is an effective bottom-up technique to assemble well-organized one-to threedimensional structures, wherein the interparticle connections can be controlled at the single-particle level. [44][45][46][47] From the application standpoint, metal nanoparticles are one of the most frequently studied inorganic materials because of their distinct combination of properties, which impart unique functionality to the nanotechnology-based devices. 48,49 We previously reported on the synthesis of a gold nanoparticle (AuNP) array prepared via a single-step procedure, wherein alkanethiols were self-assembled to deposit AuNPs on a plastic substrate, as shown in Fig.…”
Section: Molecular Bridging Among Aunpsmentioning
confidence: 99%
“…Moreover, one-or two-dimensional arrangements of nanoparticles have also evolved with respect to their pathognomonic optical characteristics, since metal nanoparticles have distinctive optical characteristics. [126][127][128] Some promising results have suggested that arrangement and nanospace may be useful in optical biosensing.…”
Section: Nanogap Electrodementioning
confidence: 99%